Feminist economics: Theoretical and political dimensions feminist economics - Agenjo-Calderón, Astrid; Gálvez-Muñoz, Lina (American Journal of Economics and Sociology, 2019)
Feminist economics is a school of economic thought and political action that gained important visibility during the 1990s, although its origins can be dated back to the mid-19th century. Since then, feminist economics has developed its own concepts, analytical frameworks, and methodologies. With gender as a central category, it seeks a more integral and humane comprehension of the economy and of the processes of inclusion and exclusion taking place in it. In addition, feminist economics has grown into a political practice that aims at improving the functioning of the economic system so that all people can have access to a dignified life on the basis of equality. This article presents a general systematization of these theoretical and political dimensions, particularly focusing on the critique of the neoclassical paradigm and its political correlates. We connect the epistemological, methodological, and conceptual contributions of feminist economics, as well as its propositions for transformative action, to specific debates on economic issues, such as the ecological emergency, crisis and austerity, the commodification of life, and the liberalization of trade.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; genre; identités LGBTQIA2+; politique; périodes historiques; ressource en ligne; sciences de la gestion; sciences humaines; sociologie; thématiques; économie; égalité des sexes

Gendered paths to asset accumulation? Markets, savings, and credit in developing countries - Catanzarite, Zachary; Diana, Carmen Diana; Doss, Cheryl D.; Oduro, Abena D.; Suchitra, J. Y.; Swaminathan, Hema (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
https://www.feministeconomics.net
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; femmes*; inégalités; microcrédit; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie

Intégrer la dimension de genre dans le développement de clusters - Département du commerce, des investissements et de l'innovation; Organisation des Nations Unies pour le développement industriel (ONUDI, 2019)
Keywords: EDI; OFDIG; afrique; approches et analyses; asie; autodétermination; discipline; entrepreneuriat; genre; identités LGBTQIA2+; international; rapports sociaux de sexe; régions géographiques; sciences de la gestion; thématiques; économie; égalité des sexes

L’économie solidaire sous le prisme du genre: une analyse critique et possibiliste - Guérin, Isabelle; Hillenkamp, Isabelle; Verschuur, Christine (Revue Française de Socio-Économie, 2019)
Cet article propose d’étudier l’économie solidaire sous le prisme du genre à partir d’un double regard, critique et possibiliste. Ce double regard, inspiré à la fois de l’économie substantive polanyienne et des recherches féministes, éclaire la manière dont les pratiques d’économie solidaire renouvellent l’économique et le politique, compris ici à la fois comme catégories d’action et de pensée. Il met aussi en lumière les chemins multiples et sinueux de l’émancipation, fruit d’un entremêlement entre principes d’échange dont l’équilibre est en renouvellement permanent.
https://rfse.univ-lille.fr
Keywords: OFDIG; approches et analyses; discipline; genre; identités LGBTQIA2+; inégalités; pouvoir; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; économie; économie solidaire

Big data for (not so) small loans: Technological infrastructures and the massification of fringe finance - Langevin, Marie (Review of International Political Economy, 2019)
This article examines the evolution of the sociotechnical systems that is leading to a massive increase in the overall indebtedness of marginalized populations in the Global South. I analyze the processes through which Big Data (or alternative data) technologies are transforming the infrastructure of fringe finance, the nature of its power relations, and its capacities. The article identifies the consequences of these technological transformations on financial practices and illustrates the qualitative nature of the changes involved. I propose that while these innovations have increased the power of this market to capture value, they have also increased risks to indebted populations and the infrastructure's stability. I argue that these financial practices, enhanced by the power of Big Data, have made the infrastructure of fringe finance dangerously hermetic to careful consideration of the productive capacities of those being targeted for inclusion into the formal financial system, thereby making it potentially dysfunctional.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; inclusion financière; périodes historiques; ressource en ligne; sciences de la gestion; économie

Les femmes, l’entreprise et le droit 2019: une décennie de réformes - World Bank Group (World Bank, 2019)
The World Bank Group’s Women, Business and the Law examines laws and regulations affecting women’s prospects as entrepreneurs and employees across 187 economies. Its goal is to inform policy discussions on how to remove legal restrictions on women and promote research on how to improve women’s economic inclusion. Women, Business and the Law 2019: A Decade of Reform introduces a new index measuring legal rights for women throughout their working lives in 187 economies. The index is composed of 35 data points grouped into eight indicators. The data covers a 10-year period not only to understand the current situation but to see how laws affecting women’s equality of opportunity have evolved over time. The index assesses economic rights at milestones spanning the arc of a woman’s working life: the ability to move freely; starting a job; getting paid; legal capacity within marriage; having children; running a business; managing assets; and getting a pension.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; discipline; droits des femmes*; entrepreneuriat; femmes*; périodes historiques; sciences de la gestion; thématiques; économie; égalité des sexes